PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI FOTOSINTESIS KELAS IV SDN SIKUMANA 2 - Maria Jesica Karolina Meo; Moses K. Tokan; Maxsel Koro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted to answer the problem of low student learning outcomes on photosynthesis material in class IV SDN Sikumana 2. Based on the results of initial observations, it is known that the learning process is dominated by the teacher and does not involve students actively. This research is a Classroom Action Research (PTK) conducted in two cycles, with 20 students as the research subjects. Data collection techniques include observation of teacher and student activities, and learning outcomes tests. The results showed that the application of the Problem Based Learning (PBL) learning model was able to significantly improve student learning outcomes, marked by an increase in the average score from 53.32 in cycle I to 81.05 in cycle II. The level of learning completeness also increased from 35% to 85%. From these results, it can be concluded that the Problem Based Learning (PBL) learning model is effective in improving student learning outcomes on photosynthesis material. This model encourages students to be active, think critically, and work together in groups. The findings recommend that problem-based learning be integrated in IPAS subjects in elementary schools, accompanied by periodic teacher training to support the implementation. Keywords: Problem-Based Learning; Photosynthesis; Learning Outcomes